2022
DOI: 10.3390/foods11091265
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality, Antioxidant, Microstructural and Sensory Properties of Spontaneously Fermented Gluten-Free Finger Millet Biscuits

Abstract: Finger millet (FM) is a nutritious and gluten-free cereal grain which is rich in dietary fibre, minerals and antioxidant properties, thereby making it an ideal raw material for preparing gluten-free foods for people suffering from celiac disease. Spontaneous fermentation of FM grains has shown improved nutritional and functional properties of its flour and can be used as a functional ingredient for gluten free biscuits. The aim of this study was to determine the effect of spontaneous fermentation (SF) on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 72 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the food matrix and ingredients of bakery products can largely modify mineral absorption [ 9 ]. Regarding this, it should also be considered that the bakery process using different raising agents between Digestive and Maria types could contribute to differences in mineral availability from the matrix [ 35 ]. In terms of labelling, the biscuits of this study cannot be considered dietary sources high in either iron or calcium; however, considering the mineral availability of biscuits, they can be considered a good option to provide calcium and iron in the diet.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the food matrix and ingredients of bakery products can largely modify mineral absorption [ 9 ]. Regarding this, it should also be considered that the bakery process using different raising agents between Digestive and Maria types could contribute to differences in mineral availability from the matrix [ 35 ]. In terms of labelling, the biscuits of this study cannot be considered dietary sources high in either iron or calcium; however, considering the mineral availability of biscuits, they can be considered a good option to provide calcium and iron in the diet.…”
Section: Resultsmentioning
confidence: 99%
“…Baking also induces changes in the bioactive compounds. According to Mudau et al (2022), baking temperature ruptures cell walls, resulting in an increase in the antioxidant activity of baked items. Kewuyemi et al (2023) observed differences in the antioxidant activity of free extracts from conventionally baked biscuits and 3D-printed biscuits (Figure 7), which was attributed to increased heat and mass transfer that produced bioactive compounds other than polyphenols or Maillard-reaction products with strong antioxidant activities.…”
Section: Bakingmentioning
confidence: 99%
“…In the case of BP, this reduction may be due to the separation of fatty acids from fat, resulting in decreased fat content in the processed millets. The decrease in fat content during natural fermentation (FP) could be linked to the heightened activity of lipolytic enzymes, which break down fat constituents into glycerol and fatty acids through hydrolysis (Mudau et al, 2022). In the case of SP, the decline in crude fat content can be attributed to the diffusion and rupture of fat globules within the gelatinized dense starchy endosperm, making fats less accessible and extractable during the estimation process (Otegbayo et al, 2001).…”
Section: Effect Of Treatments On Proximate Compositionmentioning
confidence: 99%